Blue Ocean Strategy for Preserving Javanese Script through Islamic Education Management - Bigovic, Aliya Izet; Na'imah; Mentari, Inggi Eka Ria; Efendi, Ahmad Nawawi; Ma'ruf, Muhammad Hasan; Anggreni, Rossa (HEUTAGOGIA: Journal of Islamic Education, 2024)
Abstract: This study explores the application of the Blue Ocean Strategy in preserving the Javanese script through educational institutions. In this context, the strategy is utilized to develop a new, more effective approach to increasing students' interest in learning the Javanese script. A qualitative methodology is employed, with interviews serving as the primary instrument to assess students' awareness and responses to the implemented learning methods. The findings indicate that the methods used in the examined educational institution are more accessible and comprehensible for students compared to traditional Javanese script instruction commonly practiced in elementary to high schools. This conclusion is based on interview data showing heightened student interest in the Javanese script as a result of a more innovative and adaptive teaching approach. Although the study does not report a specific increase—such as 35% or 40%—in interest, the interviews suggest that the implemented methods enhance students' enthusiasm and understanding of the script. The study implies that innovation in teaching the Javanese script can serve as an effective strategy for cultural preservation. Consequently, the Blue Ocean Strategy offers a relevant model for educational institutions seeking to develop more engaging and accessible learning experiences for students.   Abstrak: Penelitian ini membahas penerapan strategi Blue Ocean dalam pelestarian aksara Jawa melalui lembaga pendidikan. Dalam konteks ini, strategi Blue Ocean digunakan untuk menciptakan pendekatan baru yang lebih efektif dalam meningkatkan ketertarikan peserta didik terhadap pembelajaran aksara Jawa. Penelitian ini menggunakan pendekatan kualitatif dengan metode wawancara sebagai instrumen utama untuk mengukur kesadaran dan respons peserta didik terhadap metode pembelajaran yang diterapkan. Hasil penelitian menunjukkan bahwa metode yang digunakan di lembaga pendidikan yang menjadi objek penelitian lebih mudah dipahami oleh peserta didik dibandingkan dengan metode pembelajaran aksara Jawa yang umum diterapkan di tingkat SD hingga SMA. Temuan ini didasarkan pada wawancara yang mengungkapkan adanya peningkatan ketertarikan peserta didik terhadap aksara Jawa karena pendekatan yang lebih inovatif dan adaptif. Data wawancara menunjukkan bahwa metode yang diterapkan mampu meningkatkan minat dan pemahaman peserta didik terhadap aksara Jawa. Implikasi dari penelitian ini menunjukkan bahwa inovasi dalam metode pembelajaran aksara Jawa dapat menjadi strategi yang efektif dalam upaya pelestarian budaya. Oleh karena itu, pendekatan Blue Ocean dapat menjadi model yang relevan bagi institusi pendidikan dalam mengembangkan strategi pembelajaran yang lebih menarik dan mudah diakses oleh peserta didik.